Peptide receptor radionuclide therapy with 177Lu-DOTA-octreotate: dosimetry, nephrotoxicity, and the effect of hematological toxicity on survival. Issue 3 (March 2018) - Löser, Anastassia; Schwarzenböck, Sarah M.; Heuschkel, Martin; Willenberg, Holger S.; Krause, Bernd J.; Kurth, Jens
Abstract : Objectives: Peptide receptor radionuclide therapy (PRRT) with lutetium-177 ( 177 Lu)-DOTATATE is regarded as a safe treatment option with promising results for patients with neuroendocrine neoplasia (NEN). We aimed to study the absorbed organ and tumor doses, the renal and hematological toxicity as well as their mutual interaction. Another aim was the identification of adverse effects as possible predictors which may affect survival. Methods: A total of 30 (14 female and 16 male) patients with inoperable/metastatic NEN were treated with 7.4 GBq of 177 Lu-DOTATATE. Occurrence of renal and hematological toxicity wasretrospectively studied. Morever, we examined the effects of hematological toxicity on survival after 177 Lu-DOTATATE-PRRT. Results: In 49 treatment cycles, the mean absorbed dose to the kidneys was 5.13±2.12, 4.49±2.49 Gy to the liver, and 14.44±8.97 Gy to the spleen, whereas tumor lesions absorbed a mean dose of 31.43±36.86 Gy. Comparing different localizations of metastases, no significant differences in absorbed dose were observed. Clinical response status revealed regressive disease in 47.6%, stable disease in 38.1%, and progressive disease in 14.3% of cases ( n =21). Biochemically, 81.3% of patients showed reduced serotonin values ( n =16; P <0.05) following 177 Lu-DOTATATE-PRRT. No severe subacute renal or hematological toxicity occurred (one Common Terminology Criteria for Adverse Events-grade 3 for thrombocytopenia and another one for leukocytopenia). No statistically significant relation between baseline kidney function and post-therapeutic hematological changes was identified. Conclusion: The findings indicate that 177 Lu-DOTATATE-PRRT is a safe and effective treatment method for patients with NEN. Moreover, these data strongly suggest that hematological parameters may affect survival so a further re-evaluation in prospective studies is warranted. Abstract : Supplemental Digital Content is available in the text.